REFORMS IN THE SPHERE OF LEGAL SERVICES IN UZBEKISTAN - Salimova Diyora Bakhtiyorjon kizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation. Legal services that ensuring the protection of the rights and interests of citizens, play an important role in modern society. They are becoming an increasingly integral part of our daily lives and business process. In this article we will analyze the experience of legal services both in Uzbekistan and abroad, identify best practices and approaches to improving the quality of legal services.